Kapasitas Pengelolaan Desa Wisata Religius Bongo Kabupaten Gorontalo - Yumanraya Noho (JURNAL NASIONAL PARIWISATA, 2014)
The study was conducted by using descriptive qualitative method, by focus on the questions; “How are the individual and organizational capacities level of managers in managing tourism village?” The data obtained through interview, observation, and documentation techniques to identify and describe the capacity of managers both the advantages and the shortcomings that could hinder the tourism village management. The results showed that mostly of local managers are less of ability to show a high capacity in managing tourism. At the individual level there are sufficient capacities both in the aspect of awareness for pioneering the development of tourism potential and ability to grow the business souvenirs. But in the aspects of knowledge and understanding the concept of religious tourism, attraction management, and service towards tourists were lack and need to be improved. At organizational level, the managers have been able to establish a local non-governmental organization named PKBM Yotama that aimed to train and assist people in entrepreneurial and tourism activities. Unfortunately, these institutions have so many weaknesses in coordination system and showed a dominant leadership model by the founder of the institution in making variety rules and policies related to the management of tourism village. In the external partnerships aspect there were good ability of managers although there were still less amount of partners they have. Last, in promotional efforts, the managers were already able to promote their village through printed text, electronic and internet. Unfortunately they weren’t able to expand the market to domestic and foreign tourists.